A first report on biodiesel production from Aglaia korthalsii seed oil using waste marine barnacle as a solid catalyst - Intan Shafinaz, Abd Manaf; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan; Gaanty Pragas, Maniam (Elsevier B.V., 2018)
Feedstock cost is one of the main considerations in biodiesel production and researchers intensively searching for a low cost feedstock in order to make the process viable. This study reports the use of Aglaia korthalsii seed oil as a potential feedstock for biodiesel production using waste marine barnacle as a solid catalyst. A. korthalsii with oil content of 16.2 ± 0.18 wt.% was subjected to transesterification using barnacle (a source of CaO) as a solid base catalyst. The catalyst was characterized using TGA, XRD and FESEM; upon calcination CaCO3 turned into CaO, the species that catalyze the transesterification reaction. Parametric optimization under Central Composite Design revealed that the optimal reaction conditions are as follow: 12.2:1 MeOH:oil molar ratio and 4.7 wt.% catalyst at 65 °C, 3 h reaction duration, under which A. korthalsii oil was successfully converted into methyl ester (ME) with highest conversion of 97.12 ± 0.49%. The catalyst could be reused for four times, maintaining methyl ester content at 95.83% and the product meets the key specifications for biodiesel.